Operation and performance of Brayton Pumped Thermal Energy Storage with additional latent storage. (15th April 2022) - Albert, Max; Ma, Zhiwei; Bao, Huashan; Roskilly, Anthony Paul
Abstract: Pumped Thermal Energy Storage (PTES) is an increasingly attractive area of research due to its multidimensional advantages over other grid scale electricity storage technologies. This paper built a model and numerically studied the performance of an Argon based Brayton type PTES system. The model was used to optimise total work output and round-trip efficiency of the system. The aspect ratio of the thermal storage tanks and operation of packed bed segmentation have been varied to assess their impacts on round-trip efficiency. Longer and thinner tanks were found to increase efficiency, with the hot tank length affecting system performance to a greater extent than the cold tank. Larger 'temperature ratio' in segmentation operation were found to develop higher round-trip efficiency, with higher exit working fluid temperature from hot storage over a shorter duration demonstrating better performance. Key features describing the power output were identified as the duration of the region of maximum power and the steepness of the 'power front'. To maximise the duration of the high power region and decrease the width of the power front, additional latent heat storage was used, the effect of which on round-trip efficiency was then assessed with predicted efficiencies of up to 80% using isentropic reciprocating compressor/expander architecture, which is close to the theoretically predicted limit. Highlights: A numerical study on Argon based Brayton Pumped Thermal Energy Storage. Optimisation of total work output and round-trip efficiency. Additional latent heat storage was used. 80% round-trip efficiency was achieved.